A framework for the automated generation of paradigm-adaptive summaries of games. (2017) - Sandesh, B.J.; Srinivasa, Gowri
We present a framework to analyse text streams with minute details of a game and generate summaries for multiple paradigms of desired lengths (as determined by the user). Multiple paradigms refer to a summary that is player-specic, team-specic, event-specic (such as all the goals, sixes, home-runs, etc., in a game, depending on the sport), etc. The summary generation is based on building a dictionary of words specic to the sport to be able to recognise events in the game. As a next step, inputs are solicited from the sports fan with regard to the paradigm they are interested in and length of the summary that interests them. Based on these inputs, a template for the desired summary is generated. A detailed commentary of the game is mined and ltered for the events in the game that are related to the query. These events are then used to instantiate the template with appropriate descriptors. A novel feature of the template generation and instantiation is that a framework of sentences and appropriate descriptors is created based on a stochastic process that selects from a viable pool of alternatives to ensure variety in the summary that is generated. The framework has been tested on commentary from cricket games, that can be a few hours long (Twenty20 or T20 format) to five days long (test matches). A qualitative assessment of the summaries through human ratings is found to be consistent, with scores being equal to or in excess of 3 on a scale of 1-5 for all the parameters tested.